IMPLEMENTASI DESIGN PATTERN MODELS VIEW CONTROLLER (MVC) PADA APLIKASI PERPUSTAKAAN STMIK KHARISMA MAKASSAR BERBASIS WEB - Evelyn Wilbert Wijaya; Moh. Sofyan S. Thayf; Sukmawaty (STMIK KHARISMA Makassar, 2019)
STMIK KHARISMA Makassar previously had implemented a web-based library application but still using native, hadn’t used the latest server, the process of recording loan books still manual and uncontrolled. The purpose of this study was to design the STMIK KHARISMA Makassar Library Information System using MVC Design Pattern. In this study, the author made an application using the PHP programming language. The process of collecting data uses the interview method. From the results of the tests conducted, the authors draw the conclusion that the application runs as expected because the display menu is displayed well, provides ease of use, good use value of the application, and the service functions provided are quite good.